Manifestasi Supremasi Hukum : Modifikasi Football Spectators Act (FSA) sebagai Instrumen Kontrol Bagi Suporter Sepak Bola di Indonesia - Dian Ayu Nurul Muthoharoh; Alfaina Sakinah; Mohamad Abduh Jerusalem (CV Rewang Rencang, 2020)
Various problems occur in the society caused by anarchism by football supporters has not been able to be completed well in mechanisms of state law. Whereas in the Indonesia Constitution had been there a guarantee from the state about human rights, such as the right to feel save, the right to life, freedom of association and assembly. But often the act of football supporters cause harm to society and the state. They damage public facilities, disrupt community activities, even cause death of a person. One mechanism that has evolved in an effort to controll football supporters is by implementing Football Spectators Act (FSA). However, Indonesia has not applying Football Spectators Act (FSA) concept in Regulation Legislation. It is encouraging the writers to research condition and any problems about football suporters and how the concept of Football Spectators Act (FSA) can be implemented as a controll for Football Suporters in Indonesia. . This study aims to analyse football suporters problems in Indonesia, to know, to understand about the concept and find modification of Football Spectators Act (FSA) as a instrument controll for football supporters in Indonesia. This is a normative-legal research that analyse the primary, secondary, and tertiary data. According to the facts, Football Spectators Act (FSA) concept should consist of preventive effort and repressive effort to resolve football supporters problems clearly. This concept should applied in to Regulation Legislation and held by government, police, Asosiasi Suporter Sepak Bola Indonesia (ASSI), community of regional supporters, and society.